2023
DOI: 10.1101/2023.10.15.562376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term dynamics of the “Serratia marcescenscomplex” in the hospital-built environment

Sonia Aracil-Gisbert,
Miguel D. Fernández-De-Bobadilla,
Natalia Guerra-Pinto
et al.

Abstract: Serratia marcescensis an opportunistic pathogen historically associated with abrupt, unpredictable, and severe outbreaks in hospital intensive care units (ICUs) and, more recently, with the spread of acquired genes encoding carbapenem resistance. However, the population biology and ecology ofS. marcescensin the hospital ecosystem is still poorly understood. Here, we combine epidemiological information of 1417Serratiaisolates collected from the sinks of a large ICU ward that underwent significant demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(112 reference statements)
1
0
0
Order By: Relevance
“…The WGS comparative analysis confirmed that six Serratia spp. BSI isolates (VIM-1 producers recovered during the last years of studied period) carried the IncL/M plasmid, harboring the same class I integron with bla VIM-1 carbapenemase gene, which had been found in previous studies from our institution ( 13 , 16 ), suggesting a considerable ability to persist ( 24 ).…”
Section: Discussionsupporting
confidence: 55%
“…The WGS comparative analysis confirmed that six Serratia spp. BSI isolates (VIM-1 producers recovered during the last years of studied period) carried the IncL/M plasmid, harboring the same class I integron with bla VIM-1 carbapenemase gene, which had been found in previous studies from our institution ( 13 , 16 ), suggesting a considerable ability to persist ( 24 ).…”
Section: Discussionsupporting
confidence: 55%